Possibilities of using rosuvastatin to achieve target level of low-density lipoprotein cholesterol in clinical practice - Yuliia A. Prus; Igor V. Sergienko (LLC "MEDIAFORMAT", 2020)
Statins are the cornerstone of therapy for hypercholesterolemia and coronary artery disease. A large number of studies have demonstrated the effectiveness of lipid-lowering therapy in preventing the progression of atherosclerosis and the development of cardiovascular diseases. The original rosuvastatin is one of the most effective statin medication in its class used to reduce low-density lipoprotein (LDL) cholesterol. The existing fears of patients and doctors about the high doses of rosuvastatin, as well as other drugs in this group, prevent the achievement of the target LDL cholesterol values, and, as a result, contribute to the progression of atherosclerosis. This article demonstrates the efficacy and safety of taking high doses of rosuvastatin in patients of different age groups with various cardiovascular events.